2016
DOI: 10.1371/journal.pone.0160359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Soluble Epoxide Hydrolase Inhibitor on Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: ObjectivesInflammation plays a key role in the pathogenesis of acute lung injury (ALI). Soluble epoxide hydrolase (sEH) is suggested as a vital pharmacologic target for inflammation. In this study, we determined whether a sEH inhibitor, AUDA, exerts lung protection in lipopolysaccharide (LPS)-induced ALI in mice.MethodsMale BALB/c mice were randomized to receive AUDA or vehicle intraperitoneal injection 4 h after LPS or phosphate buffered saline (PBS) intratracheal instillation. Samples were harvested 24 h pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Cisplatin-induced renal apoptosis was attenuated by a sEH inhibitor via EETs dependent mechanisms [6]. Moreover, LPS-induced ALI was dampened by a sEH inhibitor in a preclinical research [4]. In the present study, pulmonary inflammation and injury was significantly reduced in Semen Cassiae treated group.…”
Section: Discussionsupporting
confidence: 50%
“…Cisplatin-induced renal apoptosis was attenuated by a sEH inhibitor via EETs dependent mechanisms [6]. Moreover, LPS-induced ALI was dampened by a sEH inhibitor in a preclinical research [4]. In the present study, pulmonary inflammation and injury was significantly reduced in Semen Cassiae treated group.…”
Section: Discussionsupporting
confidence: 50%
“…In line with the major role of sEH in EET hydrolysis, inhibition of sEH or genetic deletion of Ephx2 , the gene encoding for sEH, results in increased EET levels and modifications of various EET-mediated physiological effects including blood pressure (Sinal et al 2000 ; Sun et al 2014 ), inflammation (Bettaieb et al 2014 ; Kim et al 2015 ; Tao et al 2016 ), and inflammatory pain (Inceoglu et al 2006 ). In contrast to sEH inhibitors, which elaborated over recent years (Morisseau et al 1999 ; Ulu et al 2012 ), the available mEH inhibitors have the disadvantage that they are either highly unstable [2-nonylsulfanyl-propanamide (NSPA) and elaidamide each contain an amide group and are readily metabolized by amide hydrolases (Morisseau et al 2008 )] or highly toxic (1,1,1-trichloropropene oxide, TCPO), which prevents their application in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…into rats causes a significant increase in plasma level of potent vasodilator nitric oxide (NO) within 3 h [ 32 ]; however, some reports suggest that this effect does not have to translate into lowering blood pressure [ 25 ]. As we mentioned, recent findings showed that AUDA significantly elevates levels of vasorelaxing EETs in LPS-treated mice [ 34 ]. In regard to interactions between EETs and NO, both appear to act independent; nevertheless, it was proved that EETs activate endothelial isoform of nitric oxide synthase (eNOS) [ 8 ].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, in comparison with vehicle (LPS-treated group), administration of AUDA (10 mg/kg i.p.) markedly increased EET level and dampened the activation of nuclear factor (NF)-κB in LPS-challenged mice [ 34 ]. These findings are consistent with the previous reports indicating that EETs prevent amplification of inflammatory signaling pathways by inhibition of transcription factor NF-κB and IκB kinase [ 22 ].…”
Section: Discussionmentioning
confidence: 99%